2023
DOI: 10.1002/app.53971
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of silicone‐epoxy polymer with long silicone chain

Abstract: Silicone-epoxy polymers (SEP) with different n(Si H)/n(C C) ratios were synthesized through the hydrosilylation reaction of diallyl bisphenol A epoxy resin (DADGEBA) and hydrogen-containing silicone oil (HS) with long silicone chain.The structure of SEP was characterized by Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance spectroscopy ( 1 H NMR), and gel permeation chromatography (GPC), and the compatibility of the curing system was studied by dynamic mechanical analysis (DMA) and sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The T g values of SIHOEP-0.26-1, SIHOEP-0.26-1.5, and SIHOEP-0.26-2 were 66.42 °C, 81.36 °C, and 91.26 °C, respectively. The T g range of six groups of samples was 66.42−92.9 °C, which was significantly higher than the maximum T g of the materials synthesized by Li [28] (46.25 °C). When the same hydrogencontaining silicone oil was used, the T g of the material increased with the reaction ratio increasing.…”
Section: Thermodynamic and Mechanical Propertiesmentioning
confidence: 64%
See 3 more Smart Citations
“…The T g values of SIHOEP-0.26-1, SIHOEP-0.26-1.5, and SIHOEP-0.26-2 were 66.42 °C, 81.36 °C, and 91.26 °C, respectively. The T g range of six groups of samples was 66.42−92.9 °C, which was significantly higher than the maximum T g of the materials synthesized by Li [28] (46.25 °C). When the same hydrogencontaining silicone oil was used, the T g of the material increased with the reaction ratio increasing.…”
Section: Thermodynamic and Mechanical Propertiesmentioning
confidence: 64%
“…The tensile strength was 9.92 MPa, the fracture elongation was 45.75%, and the toughness was excellent. Compared with the work of Li, [28] the tensile strength increased was 818% and the fracture elongation was increased by 90%. As the n(C = C)/n(Si−H) ratio increased, the epoxy value increased, resulting in higher density cross-linked networks.…”
Section: Mechanical Properties Of Cured Silicone-epoxy Polymermentioning
confidence: 68%
See 2 more Smart Citations
“…Double vinyl-capped polysiloxane (VPV) was used as the modified monomer to prepare the double vinyl-capped polysiloxane-modified polyacrylate (PSMA) containing a silicone chain segment. The infrared spectrum in Figure a showed that the CC stretching vibration absorption peak at approximately 1600 cm –1 was absent in the film . Furthermore, compared to the PA film, the PFSMA n :1 film showed three new absorption peaks at 1259, 1025, and 801 cm –1 corresponding to the bending vibration absorption peaks of a methyl group in Si–CH 3 , Si–O–Si stretching vibration absorption peak, and C–Si–C stretching vibration absorption peak .…”
Section: Resultsmentioning
confidence: 97%